2002
DOI: 10.1089/104303402753812458
|View full text |Cite
|
Sign up to set email alerts
|

Increased Survival and Function of SOD1 Mice After Glial Cell-Derived Neurotrophic Factor Gene Therapy

Abstract: Amyotrophic lateral sclerosis (ALS) is caused by a progressive degeneration of motor neurons. The cause of sporadic ALS is not known, but 1-2% of all cases are familial and caused by mutations in the copper-zinc superoxide dismutase (SOD1) gene. Transgenic SOD1 mice serve as a transgenic mouse model for these cases. Glial cell-derived neurotrophic factor (GDNF) has a potent trophic effect on motor neurons. Clinical trials in which growth factors have been systemically administered to ALS patients have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 31 publications
2
101
0
2
Order By: Relevance
“…Adult female SpragueDawley rats (Harlan, Indianapolis, IN, USA), weighing 150-250 g, were served as experimental subjects. Using standard techniques, 48 rats were randomly assigned to four groups and trained to run on the Economex rotarod apparatus (Columbus Instruments, Columbus, OH, USA) for 1 week prior to surgery. The day prior to surgery, locomotion was assessed on the 21-point BBB scale.…”
Section: Gene Delivery Of Adlc Virus Into Rat Spinal Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult female SpragueDawley rats (Harlan, Indianapolis, IN, USA), weighing 150-250 g, were served as experimental subjects. Using standard techniques, 48 rats were randomly assigned to four groups and trained to run on the Economex rotarod apparatus (Columbus Instruments, Columbus, OH, USA) for 1 week prior to surgery. The day prior to surgery, locomotion was assessed on the 21-point BBB scale.…”
Section: Gene Delivery Of Adlc Virus Into Rat Spinal Cordmentioning
confidence: 99%
“…The Economex rotarod apparatus has previously been utilized to efficiently assay the behavioral impact of progressive MN disease. 48 Performance on the rotarod tests both forelimb and hindlimb function as well as balance. Following establishment of the baseline motor performance at 5 r.p.m.…”
Section: Animal Behavioral Assaymentioning
confidence: 99%
“…Previous studies in animal models of motor neuron disease (SOD1, wobbler, progressive motor neuronopathy, spinal muscle atrophy) have shown that therapeutic benefits can be achieved via adenovirus-, lentivirus-, herpes simplex virus-and adeno-associated virus (AAV)-based delivery of genes such as mutant SOD1-targeted RNAi [48,49], VEGF [6], NT-3 [28], CNTF [2], GDNF [1,58], IGF-1 [34], Bcl-2 [5] and cardiotrophin-1 [13]. Clinical translation with some of these proteins has not yielded similar efficacy in human ALS patients [12,25,26,36]; however, trials have mostly involved systemic injection of protein, not viral vector-based gene delivery.…”
Section: Viral Vector Delivery As Als Therapymentioning
confidence: 99%
“…During embryonic development, approximately half of the motoneurons generated undergo programmed cell death (PCD) (Oppenheim, 1991). Motoneuron survival and differentiation depend on trophic factors secreted from target muscle fibers and Schwann cells surrounding motor axons (Bordet et al, 2001;Acsadi et al, 2002;Wang et al, 2002;Lu et al, 2003). Reductions in skeletal muscle activity improve the access of a motoneuron to target-derived trophic factors by increasing the extent to which motor axons branch and form neuromuscular synapses (Oppenheim et al, 2000b;Millecamps et al, 2001Millecamps et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%